PERATURAN DAN PROSEDUR SERTA MEKANISE PERIJINAN SENJATA API - I Wayan Suwanda; I Wayan Juliartha Suda (Universitas Mahasaraswati K. Mataram, 2021)
Advances in technology not only have a positive impact but technology can also have a negative impact on life, where technology is used as a means to commit crimes or criminal acts. If we look closely in the last few years, we are impressed and felt that people easily own firearms of various brands and types. People who have money can easily get, collect, even in an unnatural amount. It is easy for people to get firearms, of course, because the market has changed. At least, much different when compared to the decade around the 1980s. If in the past people were so proud to keep the FN rifle, now it is not so. The M-16, which is usually used on the battlefield by soldiers, has now entered the exclusive space of weapon collectors.To answer this problem, a normative legal research method is used with an approach study based on legislation, a conceptual approach. The types and sources of data used in this study are primary data and secondary data with data collection techniques through document studies where the data obtained will be analyzed deductively qualitatively. Based on the results of research and discussion that there are legal regulations in the form of regulations and procedures as well as the mechanism of the firearm licensing process